Neuronal Chemosensation and Osmotic Stress Response Converge in the Regulation of aqp-8 in C. elegans - Igual Gil, Carla; Jarius, Mirko; von Kries, Jens P.; Rohlfing, Anne-Katrin (Frontiers in Physiology, 2017)
Aquaporins occupy an essential role in sustaining the salt/water balance in various cells types and tissues. Here we present new insights into aqp-8 expression and regulation in C. elegans. We show, that upon exposure to osmotic stress, aqp-8 exhibits a distinct expression pattern within the excretory cell compared to other C. elegans aquaporins expressed. This expression is correlated to the osmolarity of the surrounding medium and can be activated physiologically by osmotic stress or genetically in mutants with constitutively active osmotic stress response. In addition, we found aqp-8 expression to be constitutively active in the TRPV channel mutant osm-9(ok1677). In a genome-wide RNAi screen we identified additional regulators of aqp-8. Many of these regulators are connected to chemosensation by the amphid neurons, e.g. odr-10 and gpa-6, and act as suppressors of aqp-8 expression. We postulate from our results, that aqp-8 plays an important role in sustaining the salt/water balance during a secondary response to hyper-osmotic stress. Upon its activation aqp-8 promotes vesicle docking to the lumen of the excretory cell and thereby enhances the ability to secrete water and transport osmotic active substances or waste products caused by protein damage. In summary aqp-8 expression and function is tightly regulated by a network consisting of the osmotic stress response, neuronal chemosensation as well as the response to protein damage. These new insights in maintaining the salt/water balance in C. elegans will help to reveal the complex homeostasis network preserved throughout species.